Macrozoobenthos of the rivers of North-Eastern Azerbaijan - Aliyev Saleh; Ahmadova Konul; Suleymanov Suleyman; Abdurrahmanova Zemfira; Farzali Shabnam (BIO Web of Conferences)
Between 2020 and 2023, an in-depth analysis was conducted on the species composition of the macrozoobenthos in the Yalama River, including its tributaries Telchay, Mukhtadyrchay, Velmirchay, and Khuraychay, as well as other significant rivers in northeastern Azerbaijan. During this period, a total of 53 species of benthic organisms, representing 14 different taxonomic groups, were identified across the rivers studied. These findings provide important insights into the biodiversity and ecological health of the region's freshwater ecosystems. Among the various groups recorded, mollusks, dragonflies, crustaceans, and chironomid larvae were particularly prominent, both in terms of species richness and their ecological significance within the aquatic habitats. These groups are crucial for understanding the dynamics of the river systems, as they play key roles in nutrient cycling, sediment stability, and the food web. The diversity of these species also reflects the environmental conditions and the unique characteristics of the rivers in this region, which may be influenced by factors such as water quality, habitat variation, and seasonal changes.